1996
DOI: 10.1177/014572179602200606
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Normative Data for the Parent Version of the Diabetes Independence Survey

Abstract: The parent version of the Diabetes Independence Survey measures parents' perceptions of their children's mastery of 38 diabetes self-care skills. The instrument was administered to 648 parents of 622 children with insulin-dependent diabetes mellitus, ages 3 and 18 years, at seven different pediatric medical centers. Data confirming the internal consistency, interrater reliability, construct validity, and concurrent validity of the instrument are presented in this paper. Age-adjusted normative data for total sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
1
29
1
Order By: Relevance
“…There was a positive correlation between SCIS scores, patient's age and the number of years since diagnosis [17] . A similar study with a larger sample size was conducted among patients with diabetes not only for children but also for parents assessing independence of their children [18] . Approximately 25% of parents of children 6 years-old, 50% of parents of children 8 years-old and 75% of parents of 14 year-old children reported that their children had mastered their disease-related skills [18] .…”
Section: Lessons From Other Subspecialtiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive correlation between SCIS scores, patient's age and the number of years since diagnosis [17] . A similar study with a larger sample size was conducted among patients with diabetes not only for children but also for parents assessing independence of their children [18] . Approximately 25% of parents of children 6 years-old, 50% of parents of children 8 years-old and 75% of parents of 14 year-old children reported that their children had mastered their disease-related skills [18] .…”
Section: Lessons From Other Subspecialtiesmentioning
confidence: 99%
“…A similar study with a larger sample size was conducted among patients with diabetes not only for children but also for parents assessing independence of their children [18] . Approximately 25% of parents of children 6 years-old, 50% of parents of children 8 years-old and 75% of parents of 14 year-old children reported that their children had mastered their disease-related skills [18] . Another tool was developed by the Boston Children's Hospital, USA to allow older children to evaluate their readiness for transition.…”
Section: Lessons From Other Subspecialtiesmentioning
confidence: 99%
“…In fact, diabetes management in the pediatric age range could perhaps best be considered as a constantly evolving relationship consisting primarily of parental responsibility for all aspects of the regimen in young children, gradual acquisition of skills by children occurring in a context of what might be called diabetes co-management, and finally the assumption of virtually all responsibility for diabetes management by the adolescent [1][2][3][4][5][6]. Historically, diabetes clinicians and educators often advocated for the rapid assumption of autonomy by children, and the goal of complete diabetes self-care independence among children was the holy grail of pediatric diabetes therapy and education [7][8][9][10].…”
Section: Supportive Involvement In Diabetes Management By Parents Andmentioning
confidence: 99%
“…In fact, there is substantial evidence that children show progressive growth in their diabetes knowledge, skills, and responsibility as they grow physically and mature cognitively [1][2][3][4][5][6][7][8]. Unfortunately, there are also many studies showing progressive, age-dependent deterioration along such dimensions as treatment adherence, diabetic control, family conflict around diabetes, and diabetes-related quality of life [11][12][13][14].…”
Section: Supportive Involvement In Diabetes Management By Parents Andmentioning
confidence: 99%
“…The extent of parent responsibility for 40 diabetes management activities from the Diabetes Independence Survey (Wysocki et al, 1996) and the Diabetes Behavior Rating Scale (McNabb et al, 1994) was reported by both parent and youth. For each task, parent and youth reported “whose job it is in your family to see that it is done” on a 5-point scale from “It’s all my job” to “It’s all my (parent’s/child’s) job.” The scale was scored to indicate the extent to which a parent had responsibility for the child’s diabetes management.…”
Section: Methodsmentioning
confidence: 99%